The association between interleukin-6 gene -174G/C single nucleotide polymorphism and sepsis: an updated meta-analysis with trial sequential analysis - Yao Chen; Yanyan Hu; Zhenju Song (BMC, 2019)
Abstract Background This article intends to explore the association between interleukin-6 gene (IL-6) -174 G/C single nucleotide polymorphism (SNP) and the risk and mortality of sepsis by conducting this updated meta-analysis with trial sequential analysis. Methods References were made to PubMed, Web of Science, China National Knowledge Infrastructure for studies available by September 2018. Each publication was screened for its eligibility and data accessible. Statistical analysis was conducted on Stata 14.1 and TSA software 0.9.5.10 Beta Results Twenty studies (including 3282 cases and 4926 controls) and eight studies (including 610 cases and 1856 controls) were respectively enrolled in the analysis on the association between IL-6-174 G/C polymorphism and the risk and mortality of sepsis. The results did not present any association between IL-6-174 G/C polymorphism and the risk and mortality of sepsis. An exception was that IL-6-174 G/C polymorphism was correlated with worse outcome in non-adults in recessive model, co-dominant model (CC vs. GG) and allelic model, while trial sequential analysis revealed it could be a false positive result nevertheless. Conclusions IL-6-174 G/C polymorphism is not associated with the risk and mortality of sepsis. Trial sequential analysis showed that a large sample size was needed to get a more reliable result of the association between IL-6-174 G/C polymorphism and sepsis in non-adults.